A. Mattelart, & A. Vitalis. De Orwell al cibercontrol. Barcelona: Gedisa, 2015 - Gómez-Castillo, Harvey (Visión electrónica, 2018)
A. Mattelart, & A. Vitalis. De Orwell al cibercontrol. Barcelona: Gedisa, 2015 ES